Who is Lonely in the EU’s Loneliest Nation?: A Post-pandemic Examination of Loneliness among the Adult Population in Ireland, and Associations with Mental Health - Mohan, Gretta (Statistical and Social Inquiry Society of Ireland, 2025)
This paper investigates the prevalence and correlates of loneliness in Ireland, a nation identified as having the highest reported rate of loneliness within the European Union in a 2022 survey. Utilising nationally representative cross-sectional data from the Healthy Ireland initiative, collected in 2021 and 2023, this research explores the demographic and psychosocial factors associated with loneliness and its impact on mental health and quality of life. In 2021, 5.9% of respondents reported experiencing acute loneliness (often/always), with 20.2% reporting experiencing loneliness at least some of the time. In 2023, these figures reduced to 3.9% and 13.7% respectively. Regression analysis revealed strong associations between frequent loneliness and being female, having few social supports, as well as probable mental health issues. There was also evidence that younger people (15-29 years), those with a disability, and those not born in Ireland had greater likelihoods of experiencing loneliness. Being married, in good health, and participating in social groups was protective against loneliness. Acute experiences of loneliness were estimated to increase the probability of mental health issues by 35.6 percentage points. Both frequent and occasional loneliness were negatively associated with quality of life, with the association being stronger for acute loneliness. These findings highlight the significant impact of loneliness on mental wellbeing and quality of life, emphasising the need for targeted interventions and policy development to strengthen social connections and promote mental health across all age groups in Ireland.
read before the Society, 27th March 2025 - Barrington Lecture 2024/25
Keywords: loneliness; mental health; quality of life; social connectedness; Ireland; 314.15